Tingkat Kecemasan pada Pembelajaran Senam Lantai Kayang - Hanum Izzul Hanan; Lusiana; Syarifah Zahra; Yudhi Purnama (Jurusan Pendidikan Kesehatan dan Rekreasi, 2022)
Background: Observations in the field show that students are less comfortable and less confident when practicing the Kayang movement in floor gymnastics learning of physical education. This study aims to determine the level of anxiety learning bridge up floor gymnastics in class X students at SMA Negeri 8 Semarang with each factor. Methods: This quantitative research uses a survey approach to obtain data with a questionnaire as the data collection instrument. The sampling technique used purposive sampling technique, as many as 133 students were used as research samples. Results: The results showed that the level of anxiety of students in learning gymnastics on the bridge up floor was influenced by psychological factors in the very low category of 9 students, low 34 students, 45 students moderate, 36 students high, and very high 9 students. While the anxiety level of physiological factors in the very low category is 14 students, the low category is 26 students, the medium category is 50 students, the high category is 36 students, and the very high category is 7 students. Conclusions: Physical education teachers are expected to be able to use a variety of appropriate methods so that students are able to practice the bridge up movements in floor gymnastics comfortably and confidently.